Characterization, expression, and functional analysis of testis-specific serine/threonine kinase 1 (Tssk1) in the pen shell Atrina pectinata. Issue 2 (2nd April 2016) - Li, Hao-Hao; Kong, Ling-Feng; Yu, Ruihai; Yu, Hong; Li, Qi
Abstract: Testis-specific serine/threonine kinase 1 ( Tssk1 ) was named since its function was determined in mouse spermiogenesis. In our research, we cloned a homolog of the pen shell Atrina pectinata Tssk1, ApTssk1, and determined its expression characteristics at mRNA. The full length of ApTssk1 cDNA was 1517 bp, with an open reading frame of 1089 bp (58–1146), which encodes a peptide including 362 amino acids. The homologous analysis indicated that the deduced amino acid sequences of ApTssk1 shared a close identity with other reported Tssk1 . In addition, the highly conserved fragment containing a serine/threonine protein kinase catalytic (S-TKc) domain was predicted to exist in ApTssk1 . Results from the RT-qPCR display that ApTssk1 was only transcribed in the male gonad of A. pectinata, and was highest in the mature testis. Therefore, this study indicated that ApTssk1 might play a functional role during spermatogenesis in A. pectinata .